PENGARUH TEMPERATUR NUKLEASI TERHADAP GEOMETRI PRODUK MAGNESIUM KARBONAT DARI BAHAN BAKU DOLOMIT MADURA[Effect of Temperature on The Geometric Product Nucleation Magnesium Carbonate of Raw Materials Dolomite Madura] - Solihin, Solihin; Arini, Tri; Febriana, Eni (Jurnal Metalurgi, 2013)
Madura Dolomite has been characterized and processed through a combination of pyro and hydrometallurgical processes to produce magnesium carbonate. The elemental composition ratio of Madura Dolomite is Ca0.6M0.4gCO3. The shape of magnesium carbonate nucleated at 30 and 50 °C is elongated trigonal with thickness 1-3 microns, whereas another sample that nucleated at a 90 °C is in the fform of sheet with thickness 70-140 nanometer. The Difference in geometry of products is the result of the competition between kinetic force of water molecules movement and magnesium cohesive forces in the magnesium-rich solution. The product resulted for this process is magnesium carbonate with carbon dioxide excess and small amount calsium carbonate.